Estudo da indução da grafitização da resina fenólica fenol/formaldeído - Renda, Carmen Greice (2019)
Among the probable carbon sources, there are the polymers, as the phenolic resin, which produces residual carbon around 60% wt./wt. after thermal treatment. It is classified as non-graphitizable, because it has not graphitic lamellaes until temperatures between 2600°C and 3000°C. To organize carbon in temperatures around 1000°C, the catalytic graphitization was suggested, where the phenolic resin receives metallic and/or inorganic agents. Thus, three resins received the agents (ferrocene, boric acid and exfoliated graphite) and they were compared, in specific conditions of processing, to induce turbostratic or graphitic structures. Turbostratic structures have organization beyond 1 nm and graphitic fragments or graphene sheets stacked in almost parallel organizations. Graphitic structures have parallel sheets stacked. Phenolic resins with any graphitic organization would be useful in refractories or for technological applications, depending on the agents used for this induction. Materials with higher lamellae organization could reduce production costs, polydispersivity and increase their efficiency. The study was divided in three stages. In the first stage, some of the proposed procedures proved viability to this route. The best results of the organization level were between 58 and 61% and were obtained for the ferrocene agent, with thermal treatment with more isothermic steps until 1000°C/5h. After the second treatment, until 1400°C/5h, were between 60 and 65%. In the second stage was evaluated the mixing procedure in the carbon organization, the higher organization (70%) was inducted with laboratory stirrer and ultrasonic mixer, with the synthesized modified-novolak resin and ferrocene. In the third stage, the systematically evaluating the thermal decomposition of ferrocene showed phases with carbon (amorphous, turbostratic and graphitic) and with iron (hematite, maghemite, cementite and gamma-iron) and structures type hollow-like onion carbon with magnetic properties were obtained. The results open new possibilites of applications in materials engineering.